Espectrometria de fluorescência de raios x na caracterização e predição de atributos dos solos do planalto ocidental paulista - Costa, Milene Moara Reis (2022)
Understanding and quantitative design of elements quantified by X-Ray Fluorescence (XRF) and the spatial variability of soil properties are important for the development of specific management of soil and agricultural crops. Thus, the study was developed with the purpose of evaluating the potential of XRF in the quantification and mapping of Fe, Si, and Al in soils of the Western Paulista Plateau (WPP) soils. A total of 262 soil samples from the weathering of basaltic rock — Serra Geral (SG) and sandstone — Vale do Rio do Peixe (VRP) were collected in the 0.0–0.2 m layer. The total content of Fe, Si and Al was measured by XRF and compared by the traditional chemical method, sulfur digestion (H2SO4). Predictive measures were obtained by machine learning analysis — Randon Forest. The results were submitted to descriptive statistical and geostatistical analysis. The geostatistical technique allowed to describe the spatial distribution of Fe, Si and Al as a covariate factor of the lithological and mineralogical variation of the study area. Then, the maps obtained by each technique were compared to obtain the error map, that is, to assess how much a technique underestimates or overestimates the content and spatial variability of Fe, Si and Al. The X-ray fluorescence allows for quantification reliability of the total Fe, Si, and Al content of soils derived from lithological complexes in the Western Paulista Plateau. The total content of SiO2, Fe2O3, and Al2O3 determined by XRF is a safe pedoindicator of the chemical composition of the Basalt and sandstone rock. The Fe, Si, and Al contents obtained by XRF help identify different geological and pedological compartments and may be an alternative technique for the development of mapping of soil attributes for specific management purposes in large areas.